Ethnicity-Specific Features of COVID-19 Among Arabs, Africans, South Asians, East Asians, and Caucasians in the United Arab Emirates - Al Zahmi, Fatmah; Habuza, Tetiana; Awawdeh, Rasha; Elshekhali, Hossam; Lee, Martin; Salamin, Nassim; Sajid, Ruhina; Kiran, Dhanya; Nihalani, Sanjay; Smetanina, Darya; Talako, Tatsiana; Neidl-Van Gorkom, Klaus; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Background: The community of Dubai Emirate is an exceptionally interesting study sample because of its unique demographic factors. Objective: To stratify the risk factors for the multi-national society of the UAE. Methods: The retrospective chart review of 560 patients sequentially admitted to inpatient care with laboratory confirmed COVID-19. We studied patients’ demographics, clinical features, laboratory results, disease severity and outcomes. The parameters were compared across different ethnic groups.To rank the ethnicity-specific disease features we employed tree-based estimators. To build a model of ethnic specificity of COVID-19 based on clinical presentation and laboratory findings on admission we trained ML classification algorithms. Results:Out of 560 patients, 43.57% are South Asians, 26.43% are Middle Easterns, 16.79% are East Asians, 10.7% are Caucasians, and 2.5% are under others. UAE nationals represent half of the Middle Eastern patients, 13% of the entire cohort. Hypertension is the most common comorbidity in COVID-19 patients. Subjective complaint of fever and cough were the chief presenting symptoms. Two thirds of the patients had either a mild disease or were asymptomatic. Only 20% of the entire cohort needed oxygen therapy, and 12% needed ICU admission. Forty patients needed invasive ventilation. 15 patients died (2.7%). In this cohort, we observed some differences in disease severity among different ethnic groups. For example, Caucasian or East-Asian COVID-19 patients tend to have a more severe disease despite a lower risk profile. In contrast to this, Middle Eastern COVID-19 patients have a higher risk factor profile but they do not differ markedly in disease severity from the other ethnic groups. There is no noticeable difference between the Middle Eastern subethnicities - Arabs and Africans - in disease severity (p=0.81). However, there are appreciable disparities in the SOFA score, D-dimer (p=0.015), fibrinogen (p=0.007) and background diseases (hypertension, p=0.003; diabetes and smoking, p=0.045) between the subethnicities. Conclusion: We observed variations in disease severity among different ethnic groups. The high accuracy (average AUC=0.9586) of the ethnicity classification model based on the laboratory and clinical findings suggests the presence of ethnic-specific disease features. Larger studies are needed to explore the role of ethnicity in COVID-19 disease features.